The Popular Supervisor Paradox: Reconstructing Supervisor Competency in Eastern Indonesia - Siti Mutmainnah; Maisyaroh; Sultoni (Al-Qalam Institute, 2026)
Educational supervision is a decisive instrument for translating national standards into classroom practice, yet its effectiveness depends on supervisory competence that is distributed unevenly across Indonesia, most acutely in the eastern region where geographical isolation and infrastructural inequality constrain developmental practice. Existing scholarship, concentrated in better-resourced western contexts and oriented toward normative competency standards, has described the eastern competency gap in fragments without reconstructing it into a coherent account that connects pattern, condition, and concept. This study aims to reconstruct the recurring pattern of supervisory competence in Eastern Indonesia, to trace the structural and ecological conditions that produce it, and to advance a conceptual interpretation of that pattern. Employing library research within a qualitative-interpretive paradigm, the study identified sources through Scopus using a PRISMA-guided selection and analysed the corpus through thematic analysis. The synthesis reveals that supervisory competence in the region is not uniformly low but unevenly developed, with relational and social capacities relatively intact while evaluative and research capacities remain underdeveloped, a configuration named the popular supervisor paradox in which high social legitimacy coexists with low technical capacity. Read ecologically, this deficit is structurally produced rather than individually owned. The study implies that transformative education and learning in disadvantaged regions depend less on monitoring supervisors than on converting their trusted social capital into analytic capability through adaptive, context-sensitive strengthening, thereby relocating the lever of educational transformation from inspection toward developmental, evidence-based supervisory practice.